Prognostic value of post thaw semen quality parameters, mitochondrial integrity and cholesterol content of sperm membrane vis-à-vis conception rate in Frieswal bulls - SRIVASTAVA, N; PANDE, MEGHA; RAJA, T V; TYAGI, S; KUMAR, SURESH; KUMAR, SUSHIL; KUMAR, RAVINDER; SIROHI, A S; CHAND, NAIMI; ARYA, S; KUMAR, AMIT; DIN, OMER (The Indian Journal of Animal Sciences, 2018)
The present study aimed to analyze the quantitative relationship of membrane cholesterol content (Chol content), mitochondrial integrity (Δψm), and quality parameters of spermatozoa (SQP) at post-thaw stage with conception rate (CR) and estimated relative conception rate (ERCR) in Frieswal bulls. For the experiment, frozen semen straws (32) were collected from the SF laboratory and CR (Total insemination 3482) was obtained from Field Progeny Testing units. Based on the CR, bulls were grouped into low, medium or high groups (G I, G II and G III, respectively). SQP, viz. viability (Eosin Nigrosin), post thaw motility, biochemical integrity of the membrane (HOS res), acrosome integrity (Giemsa, and fluorochromes fluorescein isothiocyanate Pisum sativum agglutinin and propidium iodide, respectively), chol-content, and Δψm using fluorescent probe JC-1 (5,5’,6,6’-tetrachloro- 1,1’,3,3’-tetraethylbenzimi-dazolylcarbocyanine iodide) were determined. The values thus obtained were subjected to the stepwise regression analysis using the least squares principles for each group, and the CR and ERCR were regressed on the various SQP. Pearson’s correlation coefficients were estimated between the CR and ERCR values and the various SQPs. The coefficient of determination (R2) moderately higher for all the models and ranged from 63.70–93.40% (high and medium group, respectively). High R2 value of the prediction equation for the herd and bulls with medium CR (75.9 and 93.4%, respectively) reveal their suitability to predict the CR and ERCR potential of the cryopreserved semen. Study results point to inclusion of cholesterol content and Δψm estimation in routine semen analysis before long-term storage or usage for insemination purposes.